Regulatory Cooperation in Mega-Regional Trade Agreements - Kong, Qingjiang; Chen, Weimin (American Journal of Trade and Policy, 2022)
Trade friction in the age of global value chains is primarily due to regulatory diversity. While due to the lack of disciplines in the WTO context on the exercise of regulatory powers by states, it is difficult to eradicate the diversity, regulatory cooperation is key to reducing the restraints that heterogenous regulations may impose on international trade. Recent mega-regional trade agreements have gone beyond the WTO disciplines and put forward novel and ambitious approaches to regulatory cooperation to address behind-the-border non-tariff measures. After a critical review of the new regulatory cooperation mechanisms in three mega-regional trade agreements, this article argues that these new regulatory cooperation mechanisms have spelled out a thick web of procedures that can be used to deliver better quality domestic regulations as well as enhance governmental coordination through joint institutions that monitors the consistency of proposed regulations with treaty commitments. It is still too early to assume that these new initiatives will significantly impact ameliorating the adverse effects of regulatory diversity in international trade. Nevertheless, they break new ground in international economic rule-making and hold great promise.